Elucidating the Problems of Service Delivery in the Nigerian Local Government System since the Fourth Republic - Akuche, Chukwuebuka Chukwuemeka; Akindoyin, Dare Isaac (Kashere Journal of Politics and International Relations, 2024)
Local government as the third tier of government plays a crucial role in fostering a favorable and supportive atmosphere for residents at the community level through the proficient and productive provision of services. Its importance within a state is immeasurable as it represents an essential branch of governance. Consequently, the correlation between the caliber of services citizens receive is immensely significant. This research paper delves into the dynamics of local government and its capacity for efficient service delivery, particularly focusing on local administrations in Nigeria. It emphasizes that local government stands as the primary governmental entity closest to grassroots communities, hence it is entrusted with substantial responsibilities in delivering essential social services to enhance the quality of life. However, in Nigeria, the impact of local government remains notably constrained, particularly concerning the enhancement of service delivery. Adopting the methodology of secondary data analysis and the service delivery theoretical framework, this research paper highlights several variables responsible for the problems of service delivery in the Nigerian Local Government system since the Fourth Republic. The findings of this research paper are that, political interference, corruption and mismanagement, bureaucratic bottlenecks, insecurity, political instability, insufficient funding etc are some of the problem of service delivery in the Nigerian local government system since the fourth republic. The study recommends capacity building and training, transparent budgeting and financial management, decentralization of decision-making, performance monitoring and evaluation, policy reforms and legal frameworks and the most of others in addressing the problems of service delivery in the Nigeria local government system.